Formation of aesthetic culture of personality in the socialization process - Karam, Ahmed Muayad (Київський національний університет імені Тараса Шевченка, 2018)
The article focuses on the fact that human spirituality is crucial and includes values, value orientations, based on the general culture of man, in particular on aesthetic culture. In the process of research, the cultural direction in the education of students and their socialization were highlighted. A retrospective analysis of the scientific literature was carried out, which made it possible to state that culture is a complex formation of values, activities, personal aspects and has no unambiguous and universal definition. It is found that it is precisely in the dialogue between the person and the subject that due to the aesthetic attitude of the subject, the sensual existence of the object personality is included in the cultural system. Based on the analysis of scientific publications, a schematic representation of the mechanisms of influence of aesthetic personality culture on its behavior and other types of human activity is proposed. It is proposed to outline the aesthetic personality culture as an element of the general personality culture, which provides: analysis of input (external) attitudes, norms, values through the prism of personality outlook; a synthesis based on their own cultural views, beliefs and norms of behavior; organization according to them, ways of interaction of the subject with other people, activity in the world, creative activity and self-improvement. This is the basis for the formation of the development of aesthetic personality culture, in particular, the modern specialist in the process of his professional training, socialization. It is suggested to consider aesthetic culture as an integral personal formation in the process of socialization of personality, characterized by the ability of the individual to perceive, evaluate and realize the beautiful in everyday life, nature, art.

У статті акцентовано увагу на тому що духовність людини є визначальною і включає цінності, ціннісні орієнтації, базується на загальній культурі людини, зокрема на естетичній культурі. У процесі дослідження виокремлено культурологічний напрям у вихованні студентів і їх соціалізації. Здійснено ретроспективний аналіз наукової літератури, який дозволив стверджувати, що культура є складним утворенням цінні- сних, діяльнісних, особистісних аспектів і не має однозначного й універсального визначення. З'ясовано, що саме в діалозі "людина і предмет" через естетичне ставлення суб'єкта, чуттєве буття об'єкта особистість включається в систему культури. На основі аналізу наукових публікацій запропоновано схематичне відображення механізмів впливу естетичної культури особис- тості на її поведінку та інші види діяльності людини. Естетичну культуру особистості запропоновано окреслити як елемент загальної культури особистості, який забезпечує: аналіз вхідних (зовнішніх) установок, норм, цінностей крізь призму світогляду особистості; синтез на їх основі власних культурних погля- дів, переконань та норм поведінки; організацію відповідно до них, способів взаємодії суб'єкта з іншими людьми, діяльності у світі, творчої активності та самовдосконалення. Означене є підґрунтям формування розвитку естетичної культури особистості, зокрема сучасного фахівця у процесі його професійної підготовки, соціалізації. Запропоновано естетичну культуру розглядати як інтегральне особистісне утворення у процесі соціалізації особистості, що характе- ризується здатністю індивіда сприймати, оцінювати й усвідомлювати прекрасне у повсякденному житті, природі, мистецтві.
Формування естетичної культури особистості у процесі соціалізації
Keywords: особистість; культура; естетична культура; цінності; ціннісні орієнтації.; personality; culture; aesthetic culture; values; value orientations.